First UK trial of Xenex PX-UV, an automated ultraviolet room decontamination device in a clinical haematology and bone marrow transplantation unit. Issue 2 (June 2016) - Beal, A.; Mahida, N.; Staniforth, K.; Vaughan, N.; Clarke, M.; Boswell, T.
Summary: Background: There is growing interest in the use of no-touch automated room decontamination devices within healthcare settings. Xenex PX-UV is an automated room disinfection device using pulsed ultraviolet (UV) C radiation with a short cycle time. Aim: To investigate the microbiological efficacy of this device when deployed for terminal decontamination of isolation rooms within a clinical haematology unit. Methods: The device was deployed in isolation rooms in a clinical haematology unit. Contact plates were applied to common touch points to determine aerobic total colony counts (TCCs) and samples collected using Polywipe™ sponges for detection of vancomycin-resistant enterococci (VRE). Findings: The device was easy to transport, easy to use, and it disinfected rooms rapidly. There was a 76% reduction in the TCCs following manual cleaning, with an additional 14% reduction following UV disinfection, resulting in an overall reduction of 90% in TCCs. There was a 38% reduction in the number of sites where VRE was detected, from 26 of 80 sites following manual cleaning to 16 of 80 sites with additional UV disinfection. Conclusions: The Xenex PX-UV device can offer a simple and rapid additional decontamination step for terminal disinfection of patient rooms. However, the microbiological efficacy against VRE was somewhat limited.